2008
DOI: 10.1111/j.1532-5415.2007.01610.x
|View full text |Cite
|
Sign up to set email alerts
|

Do Palliative Consultations Improve Patient Outcomes?

Abstract: Palliative consultations improve outcomes of care, and earlier consultations may confer additional benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
149
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 246 publications
(158 citation statements)
references
References 34 publications
6
149
1
2
Order By: Relevance
“…29 A multisite Veterans Administration survey of 524 family members found that patients who had an inpatient or outpatient consultation were significantly more satisfied with information, communication, access to care, emotional and spiritual support, well-being, and dignity and care at death than families of patients who did not. 34 Early referral, which can increase the use of hospice services, maximizes the value of IPC consults. Longer hospice stays improved quality of life for patients, which in turn was associated with better quality of life for caregivers.…”
Section: Patient and Family Satisfaction And Well-being After Palliatmentioning
confidence: 99%
“…29 A multisite Veterans Administration survey of 524 family members found that patients who had an inpatient or outpatient consultation were significantly more satisfied with information, communication, access to care, emotional and spiritual support, well-being, and dignity and care at death than families of patients who did not. 34 Early referral, which can increase the use of hospice services, maximizes the value of IPC consults. Longer hospice stays improved quality of life for patients, which in turn was associated with better quality of life for caregivers.…”
Section: Patient and Family Satisfaction And Well-being After Palliatmentioning
confidence: 99%
“…Early studies demonstrated clear benefit from palliative care expertise in management of pain and other symptoms associated with advanced illness, supporting caregivers, coordinating communication, and medical decision-making between clinical teams and patient/family unit, and providing comfort at end-of-life [4][5][6].…”
Section: Originsmentioning
confidence: 99%
“…Financial distress occurs due to accumulating copayments, insurance deductibles, travel costs, home care service expenses, and lost wages (National Cancer Institute, 2015;Glajchen, 2009;Yabroff et al, 2007). Early referral to palliative care has been shown to help improve the physical and psychological well-being of both patients and caregivers as well as enhance family satisfaction (Casarett et al, 2008;Gelfman et al, 2008). Spirituality has also been found to act as a safeguard against caregiver distress by helping caregivers gain a new perspective from the cancer experience and alleviate hopelessness, resulting in improved wellbeing (Ward et al, 1996;Kim et al, 2007).…”
Section: Introductionmentioning
confidence: 99%